SUPRANATIONAL EU PROGRAMS ON HIV / AIDS, DRUG ADDICTION AND ALCOHOLISM - Pavlov, Y. (Continuing Professional Education: Theory and Practice, 2019)
The article deals with current issues relating to the prevention of AIDS, prevention of addictions, particularly such as alcoholism and drug addiction in Ukraine and abroad. It is noted that although the legislation of Ukraine on HIVAIDS in line with the European law, line with the recommendations of the UN in the field of fundamental rights in the context of HIV infection and AIDS, but there are some problems, including prevention work with explanations of law, accountability both personnel and patients to ensure their healthy lifestyle,but there are some problems whose solution requires the legislation taking into account the experience of the European Union. Emphasized that the implementation of policies to prevent HIV / AIDS, drug addiction, alcoholism and other harmful addictions made under the relevant EU programs in the field of public health. Executive Agency for Health envisages development projects and programs in the EU and neighboring countries for the prevention and appropriate treatment. European Centre for Disease Prevention and Control together with the commission in implementing the Europe and Middle Asia supranational programs in control relevant partnership in favor of the fight against HIV / AIDS, drug abuse and other harmful dependencies.